Audacious Dancing: Growing Pasifika Leaders for South Auckland through the Performing Arts - Johansson, Michelle (Art/Research International, 2024)
Audacious Dancing is an evolving framework for critically considering indigenous Pasifika art-making, legacy-leaving, education, service and leadership through the lens of social justice. Located at the juncture of the performing arts and education for young Pasifika leaders in South Auckland, Aotearoa New Zealand, and drawing on indigenous scholarship in the performing arts, Audacious Dancing offers a way to consider what it means to be a ‘creative native’, learning and leading across generations, cultures and artforms. The four strands - courageous space, indigenous excellence, critical hope and powerful action - weave intergenerational indigenous knowledges with what it means to be growing up Pasifika in the largest Polynesian city in the world.